Implementasi Konsep Perawatan Berpusat pada Keluarga - Siti Wahyuni; Dessie Wanda; Happy Hayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explore Family Centered Care (FCC) and its impact on the psychological well-being of children and parents in the non-intensive pediatric care area. The method used is a systematic review by searching the literature from several online databases. The results showed that parents' perceptions of knowledge about FCC were respect and dignity, collaboration, communication and sharing of information, involvement in care, and influencing factors. The impact of the FCC on the psychological well-being of children and parents is to reduce the anxiety of children and parents and increase parental satisfaction. In conclusion, these findings provide strong evidence for understanding what is most important to parents and the impact of the FCC on positive psychological well-being for children and parents in non-intensive pediatric care areas. Keywords: Implementation, Psychological Well-being, Family-Centered Care